2009
DOI: 10.1243/13506501jet514
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemistry, tribocatalysis, and the negative-ion-radical action mechanism

Abstract: Terms such as tribochemistry, catalysis, and tribocatalysis are often used to account for various tribological findings, especially those relating to boundary lubrication. The major goal of this article is to present/discuss tribochemistry and tribocatalysis mostly in terms of the negativeion-radical action mechanism (NIRAM). This article also briefly overviews most recent books and book chapters and discusses selected physical and chemical phenomena in the boundary friction contact concerning tribochemistry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 61 publications
(81 reference statements)
1
29
0
Order By: Relevance
“…84 and 94). 108,109 Tribochemical reactions have been explained to be induced by "triboemission" of low-energy electrons (1 to 4 eV), which are emitted by chemical bond scission. 20 Triboemitted charge carriers of both polarities have been detected in experiments for different insulating materials, and the quantity of emitted charge carriers has been found to increase for higher loads (∼1 N) and surface damage.…”
Section: G Tribochemistry and The Nature Of The Triboelectric Chargementioning
confidence: 99%
See 1 more Smart Citation
“…84 and 94). 108,109 Tribochemical reactions have been explained to be induced by "triboemission" of low-energy electrons (1 to 4 eV), which are emitted by chemical bond scission. 20 Triboemitted charge carriers of both polarities have been detected in experiments for different insulating materials, and the quantity of emitted charge carriers has been found to increase for higher loads (∼1 N) and surface damage.…”
Section: G Tribochemistry and The Nature Of The Triboelectric Chargementioning
confidence: 99%
“…116 Simulations have also indicated that adsorbed water may enhance the heterolytic mechanical breaking of chemical bonds, 117 and it has been suggested that adsorbed water molecules may be decomposed tribochemically into hydrogen radicals and a hydroxyl anions by emitted triboelectrons. 109 A quantification of these mechanisms would be important for differentiating between water-based versus water-enhanced charging mechanisms.…”
Section: G Tribochemistry and The Nature Of The Triboelectric Chargementioning
confidence: 99%
“…The same is due to heterogeneous catalysis (HetCat) and tribocatalysis [11]. Principles and applications of HetCat are compiled in [12].…”
Section: Definition Of Tribochemistry For the Present Book Chaptermentioning
confidence: 99%
“…Figure 8 illustrates the NIRAM reaction cycle. Most recent review [11] is on the NIRAM approach and shows its interrelationship with tribocatalysis. The application of the NIRAM approach explains the role of exoelectrons in some relevant tribochemical reactions detailed in [29].…”
Section: Niram and Hsab (Hard And Soft Acids And Bases) And Catalyticmentioning
confidence: 99%
See 1 more Smart Citation